Effect of the algal alkaloid caulerpin on neuropeptide Y (NPY) expression in the central nervous system (CNS) of Diplodus sargus - Magliozzi, Laura (2019)
Recent studies have suggested that Mediterranean indigenous fish species are affected by bioactive metabolites coming from marine invasive species via food web interactions. In particular, both physiological and behavioural changes in the white sea bream Diplodus sargus were related to caulerpin (CAU), a bisindolic alkaloid particularly abundant in the invasive alga Caulerpa cylindracea, on which the fish actively feed. Dietary administration of CAU decreased aggressiveness in D. sargus, suggesting an anxiolytic-like effect of CAU possibly mediated by endogenous anxiolytic agents. This hypothesis is supported here by the finding of a significant increase of NPY transcriptional expression in the brain of fish fed with CAU enriched food, shedding more light on the neural mechanisms behind the altered behaviour of D. sargus.